Um processo como aquilo que decide - Ponce, Guilherme Dutra (2019)
From the notions of relation, alterity, virtuality, it is a matter of investigating a psychoanalytic listening focused more on the process than on the subject. Pieces of cases are presented to expose some of the tensions caused by this change of focus. They center on self-care, the experience of time, the body, and attachment. In problematizing the subject/object relation and the status of language, it is a question of escaping, as far as possible, from the field of representation in the analysis and investigating the processes of creation that ensue